Erlang. - ARMSTRONG, JOE (Communications of the ACM, 2010)
The article presents information on Erlang, a computer programming language available under an open-source license. It is described as a concurrent language which works well for multicore computers. Erlang was developed at the Ericsson telecommunications firm with an emphasis on fault-tolerance, and is said to use a non-defensive programming style which deals with crashes by passing only complete and self-contained messages from machine to machine. This method is described as scaling well, since it allows components to crash without affecting the overall system.